Estudos de proteção e seletividade sob a perspectiva de minigeração fotovoltaica - Ane Caroline Macedo de Oliveira (2019)
Brazil is in a scenario in which the demand for energy is growing and environmental and financial issues are obstacles to the viability of large enterprises. The role to be played by grid-connected generation units, which is called Distributed Generation (DG), is remarkable. Among the advantages presented by DG is, for example, the reduction of transported energy that implies in the reduction of electrical losses and of investments to meet new loads. Governmental incentives for this new model and the elaboration of ANEEL's Normatives Resolutions No. 482 and 687, which recognizes the figure of the energy self-producer, ensuring their free access to the electric grid, provided a large increase in the participation of DG units in the Brazilian energy market. However, the insertion of DG sources represents a major paradigm shift for conventional energy distributors regarding their planning, operation and maintenance. This is due to the installation of these DG units which transforms a previously radial electrical distribution system into a meshed one with more than one source contributing to a short circuit. This modification may significantly change the performance of distributors' short circuit protection schemes and equipment, requiring new actions to be taken to ensure their proper operation. In April 2020, the amount of photovoltaic generation systems installed power corresponds to about 93,3% among distributed generations. In this context, the objective of this work is to analyze how the photovoltaic mini-generation connection have been occurred in the electrical system, the disturbances brought by these connections, and the performance of their protection schemes. The methodology used in this work is based on a literature review and a case study for a 2,5 MVA photovoltaic mini-generation plant where the necessary analysis for connection of this type of plant to the electrical system, namely, power flow, short circuit and protection and selectivity, are shown. The choice for this plant is because the energy distributor made available all data on the feeder from the Substation, which provides greater reliability for the results obtained. These studies are performed using Easypower software version 10.0.